2014
DOI: 10.1128/jvi.00867-14
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 9-Mediated Protection of Enterovirus 71 Infection in Mice Is Due to the Release of Danger-Associated Molecular Patterns

Abstract: Enterovirus 71 (EV71), a positive-stranded RNA virus, is the major cause of hand, foot, and mouth disease (HFMD) with severe neurological symptoms. Antiviral type I interferon (alpha/beta interferon [IFN-␣/␤]) responses initiated from innate receptor signaling are inhibited by EV71-encoded proteases. It is less well understood whether EV71-induced apoptosis provides a signal to activate type I interferon responses as a host defensive mechanism. In this report, we found that EV71 alone cannot activate Toll-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 52 publications
(55 reference statements)
1
35
1
1
Order By: Relevance
“…TLR9 is also important for immune responses against EV-A71 infection as TLR9 knockout mice display more serious symptoms than wild type mice after EV-A71 infection [ 55 ]. Interestingly, EV-A71 infection cannot directly activate TLR9-mediated innate immune responses, which are stimulated by EV-A71-induced danger-associated molecular patterns (DAMPs) release.…”
Section: Innate Immunitymentioning
confidence: 99%
“…TLR9 is also important for immune responses against EV-A71 infection as TLR9 knockout mice display more serious symptoms than wild type mice after EV-A71 infection [ 55 ]. Interestingly, EV-A71 infection cannot directly activate TLR9-mediated innate immune responses, which are stimulated by EV-A71-induced danger-associated molecular patterns (DAMPs) release.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Recently it has been reported that TLR9 mediated protection in EV71 infected mice is due to the release of danger-associated molecular patterns (DAMPs). The endogenous DNA of apoptotic cells in the supernatant of EV71 infected cells is capable of activating TLR9 signaling and release of IFN-α, IFN-γ, MCP-1, TNF-α, IL-6, and IL-10 [ 111 ]. Therefore, TLR agonist may play an important role in the host defense against EV71 infection.…”
Section: Potential Antiviral Therapeuticsmentioning
confidence: 99%
“…Induction of an antiviral immune state in non-infected cells is mediated by TLR9 detection of released DAMPS from virally infected cells. This was observed for EV-A71 where an immune response was evoked in uninfected neighboring cells (Hsiao et al, 2014) as a mechanism to prevent viral spread and tissue damage. To circumvent these immune responses, EVs can influence the cell to induce autophagy which degrades the membrane bound TLR7 sensor .…”
Section: Innate Immune Response and Enterovirus Countermeasuresmentioning
confidence: 85%